Upaya Meningkatkan Kemampuan Analisis Cerpen Peserta Didik Kelas XI-B2 SMAN 9 Surabaya dengan Media Pembelajaran Mind Map - Fauziah Nabihah; Fransisca Dwi Harjanti (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study aims to describe the application of mind map learning media in improving the short story analysis ability of students of class XI-B2 SMAN 9 Surabaya. This type of research uses Classroom Action Research which consists of two cycles. This Classroom Action Research was carried out in class XI-B2 SMAN 9 Surabaya in the first semester of 2024, with research subjects consisting of 36 students. Data collection techniques used, namely through direct observation and tests. The results showed that the use of Mind Map was quite effective as an effort to improve students' short story analysis skills. This can be seen from the increase in the average score of students from cycle I (76.8) to cycle II (96). This study concludes that Mind Map not only improves analytical skills, but also learners' engagement and creativity in learning. In addition, Mind Map helps learners visualize the relationship between short story elements, so that the analysis process becomes easier to understand.